Harmonizing Religious Values, Local Culture, and Productive Zakat in Improving The Economic Welfare of Msmes at The Tebuireng Boarding Social Institution (LSPT) Jombang - Zunaidi, Arif; Adawiyah, Robiatul; Maghfiroh, Fachrial Lailatul; Rizqi, Al Zamzami Bahrur (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
The purpose of this study is to examine the impact of religious principles, local culture, and productive zakat programs on the economic well-being of micro, small, and medium enterprises (MSMEs) in Jombang. The research method entails an examination of religious principles, local culture, and field case studies. According to the findings of the study, the incorporation of religious principles offers a strong ethical foundation for MSMEs in Jombang, resulting in honest, fair, and responsible business operations. LSPT Jombang's productive zakat program, particularly the Dhuafa Mandiri program, offers mustahik with business financing and training, enhancing their economic independence. Local culture inspires MSME products, resulting in a strong local character. According to the findings of this study, the integration of religious principles, local culture, and productive zakat programs has a considerable positive impact on the economic well-being of MSMEs in Jombang. It is envisaged that by continuing to strengthen this integration and overcoming the problems that arise, MSMEs in this region will be able to thrive and make significant contributions to the local economy and community.